Total Phenolic, Total Flavonoid Contents and Biological Activities of Mentha Suaveolens subsp. timija Crude Extracts - Chater, Oumaima; Aazza, Smail; El Ghadraoui, Lahsen (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Mentha suaveolens subsp. timija is an aromatic herb with a spearmint flavor that plays an important role in the treatment of a wide range of diseases. It has various biological activities, including serving as a natural source of antioxidants and antibacterial agents. The main objective of the present study was to identify biologically active polyphenols and assess the antioxidant capacity of Mentha suaveolens subsp. timija leaves and stems using various organic solvents (hexane, ethanol, methanol) and distilled water for extraction. The antioxidant activity was determined using the ABTS, DPPH, and Total Antioxidant Capacity (TAC) free radical scavenging methods. Results revealed that the total flavonoid and phenolic content ranged from 0.3 to 14.47 mg QE/g and 0.3 to 10.86 mg QE/g, respectively, and from 1.47 to 35.34 mg GAE/g and 1.43 to 37.1 mg GAE/g for leaves and stems, respectively. The extracts exhibited significant antioxidant activity in ABTS, DPPH, and TAC assays, which increased with higher concentrations of polyphenol extracts (P ≤ 0.05). Furthermore, the plant extracts examined in this study displayed remarkable antibacterial activity, particularly against Gram-positive bacteria, with leaf extracts showing better antibacterial activity than stem extracts.